Association of age of adverse childhood experiences with thalamic volumes and post-traumatic stress disorder in adulthood - Huffman, Nickelas; Shih, Chia-Hao; Cotton, Andrew S.; Lewis, Terrence J.; Grider, Stephen; Wall, John T.; Wang, Xin; Xie, Hong (Frontiers in Behavioral Neuroscience, 2023)
Background: Adverse childhood experiences (ACEs) have been linked to brain development and mental disorders, however, the impact of the age of occurrence of ACEs on thalamic volume and post-traumatic stress disorder (PTSD) after adult trauma remains unclear. This study assessed associations between ACEs at different ages to thalamic volumes and PTSD development following acute adult trauma. Methods: 79 adult trauma survivors were recruited immediately after trauma. Within 2 weeks of the traumatic event, participants completed the PTSD Checklist (PCL) to assess PTSD symptoms, the Childhood Trauma Questionnaire (CTQ) and Childhood Age Range Stress Scale (CARSS) to evaluate ACEs and perceived stress level at preschool (<6 years old) and school (6-13 years old) ages, and structural magnetic resonance imaging (sMRI) to measure thalamic volumes. Participants were divided into three groups: those who experienced no childhood trauma or stress (non-ACEs), those who experienced childhood trauma and stress onset at preschool ages (Presch-ACEs), and those who experienced childhood trauma and stress onset at school ages (Sch-ACEs). At 3 months, participants underwent PTSD symptom evaluation using the Clinician Administered PTSD Scale (CAPS). Results: Adult trauma survivors in the Presch-ACEs group had higher CTQ and CAPS scores. In addition, survivors in the Presch-ACEs group had smaller thalamic volume compared to survivors in the non-ACEs and Sch-ACEs groups. Furthermore, smaller thalamic volume moderated a positive association between post-trauma 2-week PCL and subsequent 3-month CAPS scores. Discussion: Earlier occurrence of ACEs was associated with smaller thalamic volume, which appears to moderate a positive association between early posttraumatic stress symptom severity and PTSD development after adult trauma. This raises the possibility that early occurrence of ACEs may impact thalamic structure, specifically a reduction in thalamic volume, and that smaller thalamic volume may contribute to susceptibility to PTSD development after adult trauma.